(3TQM GdCeGdj aj GdJhMjOs - (3eLghds ((3EHQGgje Hf GdHQgGf s)
(3ChdgG (B:s
(3ai caI GdejRGf , hbhd (B" (3dG Edg EdG Gddg (B" (3ai cag CNQi s
(3BNQgG (B:s
(3fSCd Gddg GdKHGJ Ydi GdOjf hUdi Gddg Ydi eMeO hBdg hUMHg CLeYjf Je s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfXe HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJhMjO hGdedd hGdfMds